Transformational Leadership of Integrated Islamic School Principal - Rulitawati Rulitawati; Muhammad Zainuddin Nawi; Try Susanti; Try Susanti; Muhammad Yusup; Hanura Febriani; Nova Asvio (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Transformational Leadership of Integrated Islamic School PrincipalPurposing of this study was to identify or obtain information about how thetransformational leadership of school principals in improving the quality and performance of teachers in teaching activities at the Al-Ihsan Integrated Islamic School (SDIT) during the Covid-19 pandemi. This study uses a qualitative approach that is used to obtain information on decisions, constraints and consequences of the COVID-19 pandemi in teaching and learning activities at SDIT. The results of the principal transformation leadership research in improving the quality and performance of teachers in teaching activities at SDIT Al-Ihsanduring the Covid-19 pandemi include: 1) setting good examples for teachers in facing challenges during the Covid-19 pandemi; 2) providing intellectual stimuli such as providing opportunities for SDIT Al-Ihsan teachers to take part in training and counseling activities on the brave learning system; 3) teacher motivation to be able to develop bold learning methods and models; and 4) evaluate the policies that have been implemented. The principal's transformational leadership is expected to be able to overcome learning obstacles by improving communication and coordination between parents and teachers so that parents can guide their children during the learning process at home.Abstrak: Kepemimpinan Transformasional Kepala Sekolah Islam Terpadu.Tujuan dari penelitian ini adalah untuk mengidentifikasi atau memperoleh informasi tentang bagaimana kepemimpinan transformasional kepala sekolah dalam meningkatkan mutu dan kinerja guru dalam kegiatan mengajar di Sekolah Islam Terpadu (SDIT) Al-Ihsan selama masa pandemi Covid-19. Penelitian ini menggunakan pendekatan metode kualitatif yang digunakan untuk memperoleh informasi keputusan, kendala dan akibat pandemi covid 19 pada kegiatan proses belajar mengajar di SDIT. Hasil dari penelitian kepemimpinan transformasional kepala sekolah dalam meningkatkan mutu dan kinerja guru dalam kegiatan mengajar di SDIT Al-Ihsan selama masa pandemi Covid-19 ini antara lain: 1) memberikan teladan yang baik kepada guru dalam menghadapi tantangan pada masa pandemi Covid-19; 2) memberikan stimulus intelektual seperti memberikankesempatan bagi guru SDIT Al-Ihsan untuk mengikuti kegiatan pelatihan dan penyuluhan tentang sistem pembelajaran daring; 3) memotivasi guru agar mampu mengembangkan metode dan model pembelajaran daring; dan 4) melakukan evaluasi terhadap kebijakan yang sudah dilaksanakan. Kepemimpinan transformasional kepala sekolah diharapkan mampu mengatasi kendala pembelajaran daring dengan cara meningkatkan komunikasi dan koordinasi orang tua dengan guru sehingga orang tua mampu membimbing anak saat melakukan proses pembelajaran daring di rumah.